Preparing for childbirth in HPV-compromised women - Luiza R. Sakaniia; Asida A. Gurguliia; Irina M. Korsunskaia (IP Berlin A.V., 2020)
Today, human papillomavirus (HPV) is one of the most prevalent sexually transmitted infections. However, this way of transmission is not the only one. Newborns can get an infection at birth from an HPV-positive mother. Some data suggest that up to 79% of day-old children can be infected during childbirth. Not always polymerase chain reaction test for HPV in a child will be positive immediately after childbirth, since the incubation period can last up to 10 years. Studies shows correlation between the mothers HPV status during pregnancy and postpartum period and the childs risk for HPV infection. The standard therapy for HPV cannot be given to pregnant women. For them, there are alternative therapies, in particular, topical glycyrrhizic acid-containing drugs. This substance has long been known for its antiviral properties and can be safely used both during pregnancy and lactation. Our own observations of a small sample of 26 patients and 27 children over a period of 1.5 years show that the use of a glycyrrhetinic acid-containing drug a week before the expected childbirth helps prevent transmission of the virus to offspring. Also, the use of the drug after destructive therapies for vaginal papillomatosis allows to prevent rapid relapse of infection. These findings require further research. However, it can certainly be argued that patients with a history of HPV-positive status should be regularly examined, despite the fact that the effect of glycyrrhizic acid therapy persists for a long period of time.